L’expertise en question dans la gestion des risques naturels : le cas des Ruines de Séchilienne - Geneviève Decrop (Éditions en environnement VertigO, 2014)
Technical and scientific expertise has been for the past twenty years in the midst of a number of debates, following controversies in matter on sanitary and environmental risks. Under public influence, the expertise in this matter has had to progress and to offer guaranties of independence, transparency and reliability of its findings. Strangely, the field of natural hazards remained out of this movement. According to the classical model – legal-rational - the government and its experts have a stranglehold on risk assessment and preventive measures. In France, this model turns on a real « technical magistrature ». However, the expertise in this field is not free of interest ‘interference. The present article reports the case of an opaque organization of expertise on a geological movement, in the Romanche Valley, at South-East of Grenoble, with serious consequences on the exposed people and local economy.In this case, the local communities were completely dependent of the expertise, which runs in a closed circuit. But the problem of expertise has to be replaced in the questioning on public policies of natural risk prevention which are out of step with the new landscape of risk and with its future deals.